ENT600 : “Anti-Theft Security Alarm” apps / Nurul Syuhada R. Azmi, Intan Zahida Ahmad Mustaza and Nurul Asyikin Ab Wahab - R. Azmi, Nurul Syuhada; Ahmad Mustaza, Intan Zahida; Ab Wahab, Nurul Asyikin (2018)
Malaysia is said to be ranked as one of the top 10 countries in the world with the highest number of vehicle thefts. An average of 60 vehicles get stolen everyday from all over the country, said the General Insurance Association of Malaysia's (PIAM) chief executive officer Mark Lim. The issues that the team had defined was on the loss and missing of many amount of vehicles like cars, bikes and motorcycles in these days is the problem that lead to this New Product Development (NPD) project which is to create "Anti-Theft Security Alarm" Apps